Novel utilization of liquid feedstock in high velocity air fuel (HVAF) spraying to deposit solid lubricant reinforced wear resistant coatings - Ganvir Ashish; Jahagirdar Adwait Rajeev; Mulone Antonio; Örnfeldt Louise; Björklund Stefan; Klement Uta; Joshi Shrikant (ELSEVIER SCIENCE SA, 2022)
The ability to axially inject liquid feedstock has encouraged the thermal spray research community to explore this concept to deposit coatings for various next generation functional applications. The current study explores the utilization of liquid feedstock in high velocity air fuel (HVAF) spraying to deposit solid lubricant reinforced wear resistant coatings for the first time. The study successfully demonstrates the use of a powder-suspension hybrid processing approach to incorporate a solid lubricant Boron Nitride (as suspension) in a wear resistant Cr3C2-NiCr (as powder) cermet matrix. Coatings were characterized using Scanning Electron Microscopy and Raman Spectroscopy to analyze their microstructure and phase constitution. The results show that the tribological performance of the hexagonal boron nitride (hBN)-incorporated composite coating was significantly better than the traditional powder-derived Cr3C2-NiCr coating. Such hBN-incorporated composite coatings are needed to improve the mechanical properties and enhance the overall tribological performance of metallic components used in various applications, especially at high temperature such as cylinder bore, pistons, deformation tools, etc. The limitations of liquid based lubricants at high temperature motivates the use of hBN reinforced composite coatings as it can form a protective solid lubrication tribo-film. The study concludes that the emerging HVAF technology can accommodate liquid feedstock and be successfully utilized to deposit hybrid powder-suspension composite coatings to create multi length scale microstructures which can be attractive for combining different tribological attributes in the same coatings system.